Fitogeografia e estrutura das florestas estacionais deciduais no Brasil - Soares Filho, Avaldo de Oliveira (2012)
The thesis aims to contribute to the knowledge of Brazilian Dry Forests, still little studied, as much with regard to their floristic composition as to their structure. The present work, in considering Brazilian Dry Forests, follows the classification of IBGE and aims to test the hypothesis that, in spite of occurring in various regions of Brazil, the Brazilian Dry Forests show a low degree of floristic affinity, when comparing those from different regions, such as those at the borders of the Caatinga of the North-east with those from the West of Maranhão, the Cerrados of the Centre-West of Brazil or southern Brazil. Comparative studies on the floristic composition of Dry Forest were carried out in ten selected sites, where the focus was also on environmental aspects. Fieldwork was completed between 2002 and 2010 in the following areas: 1. Parque Estadual do Turvo – RS; 2. Parque Estadual do Morro do Diabo – SP; 3. Planalto Conquistense – BA; 4. Serra de Montes Altos – BA; 5. - Parque Nacional da Serra das Confusões - PI; 6. Parque Estadual Prof. Vasconcelos Sobrinho – PE; 7. Reserva Biológica Pedra Talhada – AL; 8. Parque Estadual Terra Ronca – GO; 9. Parque Estadual dos Pirineus – GO; 10. Reserva Extrativista do CIRIACO - MA. The phytosociological study was carried out in areas where the vegetation was least disturbed. 15 parcels of 30 × 10 m were chosen at walking random and all individuals with a circumference at breast height ≥ 20 cm were numbered, characterized and their height and circumference measured. Herbarium material was also collected for future identification. The following phytosociological parameters were recorded: Cover value (VC), Dominance (Do), Density (D) and Basal area (AB). The diversity of the Dry Forests was evaluated, using species number, floristic similarity and Shannon’s, Pielou’s and Simpson’s diversity indices, as well as the proportion between the number of species and number of individuals (sp/ni). From binary and species abundances matrices in the 10 Dry Forests studied, multivariate analyses of classification and ordination were carried out, as well as phytogeographic analyses, which also considered the influence of environmental factors. Historical factors such as glaciations and emergence of the continental platform were also considered in relation to the evolution of dry forests in Brazil. In all, 756 species in 243 genera and 82 families were recorded, with the Leguminosae representing 21% of the total species, Myrtaceae 9.5%, Rubiaceae 4.2%, Lauraceae 3.7%, Annonaceae 3.3% and Euphorbiaceae 3.3%. Considering all the forests together, the mean tree height was 9.6 m and the mode 7 m, with 87% of the dominant component between 6 and 15 m high, the D mean being 1,224 live individuals/ha., the AB mean 27 m2/ha, the H’ mean 3.9, sp/ni mean 0.2 and richness mean 99 species (in 0.45 ha). The proportion of dead individuals at each site fell within normal limits, indicating that the forests are in a good state of conservation. The classification of the studied forests results in large groups, with the Ciriaco Forest (border of Amazonic Forest) quite separate from the others. Also the forests from the South/South-east are in a group separate from the forests from Northeast/Centre-west Brazil. The canonical correspondence analysis show the DF separated by patterns of water deficit, associated with the Aw (tropical climate with winter rain and dry summer) and As (tropical climate with summer rain and dry winter) climes. Dry Forests which we observe today are the result of changing climates and the contraction and expansion of the continental platform as a result of sea-level changes with migration of species from the littoral to the interior and vice versa. These result in changing habitats and possible adaptation changes especially when species distributions become fragmented. Such interacting factors can result in a floristic differentiation of dry forests, with medium to high Diversity and heterogeneous phytogeographical patterns, demonstrated by the low floristic between dry forests from different regions of Brazil. The data obtained, confirm the hypothesis proposed at the outset of the project.